Assessment of Iranian Apricot Cultivars Resistant, Susceptible and Mutant to Late Spring Frost - Zeinab Nazemi; Mehrshad Zeinolabedini; Mohammad Taher Hallajian; Naser Bouzari; Parastoo Majidian; Mohammad Ali Ebrahimi (Journal of Plant Molecular Breeding, 2016)
Apricot is grown in a wide range of climatic conditions in Iran, however, it is frequently damaged by late spring frost. In this case, identification of new genotypes tolerant to cold stress is indispensably needed. The objective of this study was to evaluate the genetic population and relationships among 27 apricot accessions (Prunus armeniaca) by 30 microsatellite markers and 11 morphological traits. Based on the PIC values, the SSR loci (UDP96001, UDP96003, UDP98412 and UDP98411) were the most informative markers. The morphological traits were categorized into three components which explained 91.23% of total variation. The two-dimensional PCA plot exhibited that the highest degree of fruit quality and quantity belonged to the susceptible cultivar of Shahrood 48 which showed to be the favorable parent for the production of resistant mutants with high value of fruit traits to late spring frost. Moreover, the close relatedness of Shahrood 48 and its mutants according to the molecular analyses (including a Bayesian clustering approach and a Partial repeated bisection) confirmed the results of fruit traits analysis. The findings suggest that the wide diversity present in Iranian apricot genotypes could be used as a genetic resource for conservation and development of new cultivars resistant to late spring frost and for designing further apricot breeding programs. The promising new mutant genotypes tolerant to cold stress will be evaluated based on morphological markers in further breeding studies.